Keamanan Siber Berbasis AI untuk Mitigasi Ancaman Komputasi Kuantum - Sunarti Ekowati, Maria Atik; Darsini (Universitas Boyolali, 2025)
Cybersecurity has become a major challenge in protecting data and information systems in the rapidly evolving digital era. One emerging threat is the potential impact of quantum computing on the cryptographic algorithms currently in use. Quantum computing has the potential to weaken the resilience of conventional encryption, thereby creating vulnerabilities that could be exploited by cyberattacks. Therefore, innovation in cybersecurity systems is urgently required to anticipate these threats. This study aims to develop and evaluate a cybersecurity prototype based on Artificial Intelligence (AI) designed to protect data from quantum computing threats. The research methodology includes the development of AI algorithms for anomaly detection, system resilience testing, and quantum computing threat simulation in real-world scenarios. The results indicate that the developed AI-based system is capable of identifying potential attacks and responding more quickly than traditional security systems. Moreover, the prototype demonstrates greater resilience against attacks leveraging quantum computing capabilities. The expected outcome of this research is the establishment of a cybersecurity framework that can be implemented across various sectors, along with strategic recommendations for adopting AI in addressing future cybersecurity challenges.